TWO SOLUTIONS TO PROBLEMS: CONCRETE PAVEMENT DAMAGE AND REPAIR FROM THE PERSPECTIVE OF DESIGN OPTIMIZATION (BIM MODELING) AND MODIFIED CONCRETE MATERIALS - Barabash, Maria Serhiivna; Meiyu, Shao (Theory and practice of design, 2024)
Abstract. With the rapid development of the global economy and the accelerated pace of global integration, the pressure on transportation is increasing in all countries of the world, including, of course, in Ukraine. The existing concrete often fails to meet the expected service life and quality, which means that roads have to be rebuilt as well as a lot of road repair work, which undoubtedly increases the government’s financial expenditures and workload. There are a number of ways of solving these problems, the most frequently used and effective of which is the use of computer software for computational simulation of the road construction environment, monitoring and modification of concrete materials. Purpose. The goal of this paper is to start from the above two directions and propose two solutions to solve the problem of simulation of soil characteristics in road construction and optimization of road materials. Methodology. The research methodology is mainly based on theoretical research method and experimental method. Results. The article draws the following two results through theoretical analysis and experimental methods: a model for measuring soil characteristics using LIRA-SAPR software and the possibility and dosage of basalt fiber modified cement concrete. Scientific novelty. This article proposes for the first time a soil property modeling method based on the Winkler- Fuss and Pasternak soil models using the software LIRA-SAPR. For the first time, the performance of two specific basalt fibers from China and Ukraine were tested and verified the reinforcing effect and dosage of basalt fibers produced in Ukraine for concrete. Experiments have proven that adding 2% basalt fiber will make cement concrete have better performance. Practical relevance. The proposed modeling methodology helps to optimize the design to ensure structural stability and safety, and the in-depth knowledge of soil conditions helps to plan the construction phases more accurately, which helps to control costs and reduce delays. The response results of concrete modified with basalt fibers can be used in practical projects to enhance pavement strength.